(untitled) (Journal of International Studies, 2023)
As part of their “Look East” foreign policy, the Gulf Cooperation Council (GCC) countries have been focusing on enhancing their relations with several Asian countries, including Indonesia, which is the largest economy in Southeast Asia. The adoption of this policy has resulted in an apparent increase in cooperation between these Arab Gulf nations and Indonesia. There is a visible trend of growing cooperation between GCC countries and Indonesia, particularly during the first term of President Joko Widodo, covering areas from diplomacy, energy, and trade to investments. Although the expansion of diplomatic, energy and economic ties between both sides has been widely discussed in the literature, little attention has been paid to the public diplomacy strategies used by the GCC countries in their interactions with Indonesia. Realizing the limitations of their newly developing relationships with Indonesia and the importance of promoting a positive image to secure their political and economic interests in the region, the GCC countries are fully aware of the need for effective public diplomacy strategies. This research, therefore, aims to examine the public diplomacy strategies employed by the GCC countries towards Indonesia. These strategies can be arguably divided into four distinct groups: educational initiatives, cultural activities, religious studies and practices, as well as humanitarian aid. This study argues that while public diplomacy has increasingly become an integral part of the GCC countries’ strategies in establishing relations with Indonesia, the application of these strategies has been prevalent only among a few GCC countries in which extensive political and economic relations are already well forged with Indonesia.